How can governments help small enterprises integrate into global value chains? - Gaurav Pundir (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
Though MNE-SME linkages accelerate integration of small businesses into global value chains, FDI alone does not suffice. This Perspective argues that supportive host country policies like spurring adoption of digital tools, promoting ease of acquiring certifications, improving access to finance, and attracting investment from MNE suppliers make firms linkage-ready.
Keywords: 330